2014
DOI: 10.1371/journal.pone.0098527
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Prevents Endothelial Progenitor Cell Dysfunction Induced by Sera from Women with Preeclampsia or Conditioned Media from Hypoxic Placenta

Abstract: ContextPlacenta-derived circulating factors contribute to the maternal endothelial dysfunction underlying preeclampsia. Endothelial colony forming cells (ECFC), a sub-population of endothelial progenitor cells (EPCs), are thought to be involved in vasculogenesis and endothelial repair. Low vitamin D concentrations are associated with an increased risk for preeclampsia.ObjectiveWe hypothesized that the function of human fetal ECFCs in culture would be suppressed by exposure to preeclampsia-related factors–preec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 49 publications
2
25
0
3
Order By: Relevance
“…Indeed, it has been demonstrated that calcitriol regulated placental human chorionic gonadotropin expression [ 95 ], placental steroid hormone secretion [ 96 ], placental calbindins expression [ 97 ], and placental invasion, as indicated by the increased secretion of matrix prometaloproteinases 2 and 9 by human extravillous trophoblasts [ 98 ]. In addition, calcitriol promoted vascular endothelial growth factor and the antioxidant CuZn-superoxide dismutase expression in endothelial cells [ 99 ], and reversed the adverse effects of preeclampsia serum or conditioned medium from hypoxic placenta on endothelial colony-forming cells' capillary tube formation and migration [ 100 ]. Furthermore, calcitriol has been considered a regulator of placental inflammatory cytokines [ 93 , 101 , 102 ] ( Figure 1 ) and cytokines have been able to regulate placental CYP27B1 and CYP24A1 expression [ 92 ].…”
Section: Calcitriol In Preeclamptic Pregnancymentioning
confidence: 99%
“…Indeed, it has been demonstrated that calcitriol regulated placental human chorionic gonadotropin expression [ 95 ], placental steroid hormone secretion [ 96 ], placental calbindins expression [ 97 ], and placental invasion, as indicated by the increased secretion of matrix prometaloproteinases 2 and 9 by human extravillous trophoblasts [ 98 ]. In addition, calcitriol promoted vascular endothelial growth factor and the antioxidant CuZn-superoxide dismutase expression in endothelial cells [ 99 ], and reversed the adverse effects of preeclampsia serum or conditioned medium from hypoxic placenta on endothelial colony-forming cells' capillary tube formation and migration [ 100 ]. Furthermore, calcitriol has been considered a regulator of placental inflammatory cytokines [ 93 , 101 , 102 ] ( Figure 1 ) and cytokines have been able to regulate placental CYP27B1 and CYP24A1 expression [ 92 ].…”
Section: Calcitriol In Preeclamptic Pregnancymentioning
confidence: 99%
“…25(OH)D3 may regulate the functionality of angiogenic progenitor mononuclear cells and attenuate their reparative capability (34,35). Taken together, the findings suggest that vitamin D deficiency could coordinate the altered repair ability of progenitor mononuclear cells and inflammation in MetS.…”
Section: Discussionmentioning
confidence: 89%
“…As the bioactive form of vitamin D, 1,25(OH) 2 D 3 has immunomodulatory properties and regulates angiogenic processes by promoting secretion of vascular endothelial growth factor and expression of antioxidant CuZn superoxide dismutase through vitamin D receptor (VDR)-mediated pathways [ 53 ]. In vitro studies have shown that 1,25(OH) 2 D 3 can regulate endothelial progenitor cell migration and angiogenesis [ 54 ]. NF-κB is involved in the transcription of multiple proinflammatory cytokines, and it also plays an important role in immune responses of T helper 1 and T helper 2 cytokines.…”
Section: Discussionmentioning
confidence: 99%